2021
DOI: 10.3389/fpsyt.2021.634454
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive Hoarding Symptoms and the Role of Mindfulness Skills During Social Distancing for the COVID-19 Pandemic: An Exploratory Survey

Abstract: People reporting compulsive hoarding symptoms (CHS) have lower mindfulness skills than those without such symptoms. Mindfulness skills can have the role of a protective buffer against stressful periods. The quarantine imposed to contain the COVID-19 spread had a negative impact on daily habits and healthy behaviors (including social interactions). An increased attachment to objects might be one of the under-recognized psychological consequences of these difficult times, yet no study focused on CHS. Through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…These findings suggest that mindfulness can help achieve a "double dividend" in decreasing hoarding behavior. Although previous studies showed the potential negative influence of mindfulness on hoarding behavior (Marazziti et al, 2021), our findings identify the relationship between dispositional mindfulness and hoarding behavior from a new perspective, and reveal the "black-box" of how this relationship works.…”
Section: Theoretical Implicationscontrasting
confidence: 55%
See 4 more Smart Citations
“…These findings suggest that mindfulness can help achieve a "double dividend" in decreasing hoarding behavior. Although previous studies showed the potential negative influence of mindfulness on hoarding behavior (Marazziti et al, 2021), our findings identify the relationship between dispositional mindfulness and hoarding behavior from a new perspective, and reveal the "black-box" of how this relationship works.…”
Section: Theoretical Implicationscontrasting
confidence: 55%
“…Recent investigations have included mindfulness as a component of an intervention for obsessive-compulsive symptoms (e.g., Patel et al, 2007;Sugiura and Sugiura, 2015;Apaolaza et al, 2019), and one of the symptom dimensions is hoarding disorder. Moreover, previous research found that individuals with compulsive hoarding symptoms scored lower in the attention facet of mindfulness skills than those without such symptoms (Marazziti et al, 2021). These studies jointly suggest the negative association between mindfulness and hoarding behavior.…”
Section: Theoretical Framework and Hypotheses Mindfulness And Hoardin...mentioning
confidence: 62%
See 3 more Smart Citations